2019
DOI: 10.1093/mnras/stz504
|View full text |Cite
|
Sign up to set email alerts
|

Significant core shift variability in parsec-scale jets of active galactic nuclei

Abstract: The apparent position of jet base (core) in radio-loud active galactic nuclei changes with frequency because of synchrotron self-absorption. Studying this 'core shift' effect enables us to reconstruct properties of the jet regions close to the central engine. We report here results from core shift measurements in AGNs observed with global VLBI at 2 and 8 GHz at epochs from 1994 to 2016. Our sample contains 40 objects observed at least 10 times during that period. The core shift is determined using a new automa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 58 publications
7
102
0
Order By: Relevance
“…[42,49]. Because of variable optical depth [50], Faraday depth and higher turbulence [51], the core components demonstrate, on average, larger EVPA fluctuations [47]. In this work, we therefore concentrate only on the jet features.…”
Section: The Datamentioning
confidence: 99%
“…[42,49]. Because of variable optical depth [50], Faraday depth and higher turbulence [51], the core components demonstrate, on average, larger EVPA fluctuations [47]. In this work, we therefore concentrate only on the jet features.…”
Section: The Datamentioning
confidence: 99%
“…This assumption is weaker than the equipartition assumption. However, it could be violated during flares (Lobanov & Zensus 1999;Lisakov et al 2017;Plavin et al 2019), when region of e.g. higher plasma density is travelling along the jet.…”
Section: Re-parametrization and Additional Assumptionsmentioning
confidence: 99%
“…At the same time even these simplified approaches need measurements of the core shifts. However core shift estimates obtained using the fitting of the VLBI core with a Gaussian are biased with bias that depends on resolution (Plavin et al 2019) and observed jet parameters (Pashchenko et al, in prep.). Finke (2019) used analytical expressions for flux density and core shift of the Blandford & Königl (1979) model to estimate physical jets properties.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the apparent position of the jet base (core) in radio-loud active galactic nuclei changes with frequency due to synchrotron selfabsorption. Plavin et al (2019b) investigated 40 AGN and determined typical offsets between the core positions at 2 and 8 GHz of about 0.5 mas with a variability of the individual core positions of about 0.3 mas over ten years. At higher frequencies the core shift is less pronounced, as it follows in many cases a negative exponential distribution, leading to a core shift between X and K band of about 0.1 mas (Hada et al 2011).…”
Section: Aspects Of Core Shift Effectsmentioning
confidence: 99%
“…We are aware that there are issues related to core shift (Plavin et al 2019b), which may cause the matching procedures of identical catalogs at different frequency bands to become insufficient for a variety of candidates. However, in this publication, we demonstrate that the effect is of a random nature for catalog combinations.…”
Section: Introductionmentioning
confidence: 99%